Convergence Rate of Implicit Iteration Process and a Data Dependence Result (European Journal of Pure and Applied Mathematics, 2018)
The aim of this paper is to introduce an implicit S-iteration processand study its convergence in the framework of W-hyperbolic spaces. We showthat the implicit S-iteration process has higher rate of convergence than implicit Mann type iteration and implicit Ishikawa-type iteration processes. We present a numerical example to support the analytic result proved herein. Finally, we prove a data dependence result for a contractive type mapping using implicit S-iteration process.
Keywords: implicit iterations; convergence rate; data dependence.